Improving Hepatitis B Screening Prior to Rituximab: A Quality Improvement Project - D. Sofia Villacis-Nunez; Evan Orenstein; Phyllis Selvaggio; Kelly Rouster-Stevens; Chia-shi Wang; Amit Thakral (MDPI AG, 2023)
Rituximab, used in the treatment of some rheumatic and kidney diseases, can lead to hepatitis B virus (HBV) reactivation; HBV screening is recommended for those starting this medication. We aimed to improve by 50% the proportion of patients undergoing HBV screening by implementing multimodal interventions to support clinicians in this evidence-based practice. We conducted a quality improvement project from November 2020 to June 2022 at a tertiary care pediatric hospital system, including patients with rheumatic and/or kidney diseases starting rituximab. Multimodal interventions targeting clinicians included electronic health tools (dot phrase, display of screening recommendations and screening results in rituximab order sets/therapy plans), educational meetings, and e-mail/paper reminders. The primary outcome was the proportion of patients with complete HBV screening, while the secondary outcome was utilization of each laboratory component, tracked using statistical process control charts. Pre- and post-intervention data were compared using Fisher's test. One hundred eighty-two patients who had been prescribed rituximab were included, of which 98 (54%) were post-intervention. The proportions of patients undergoing complete HBV screening (6% vs. 44%; p < 0.001), HBsAg collection (60% vs. 79%; p = 0.006), anti-HBsAb collection (14% vs. 54%; p < 0.001), and total anti-HBcAb collection (8% vs. 52%; p < 0.001) were significantly higher in the post-intervention period. Improvement was sustained over 18 months, with shifts and/or data points above the control limits in all measures. Forty-five patients were HBV-non-immune. In this study, multimodal interventions including electronic health tools and education of the provider significantly increased the proportion of patients screened for HBV prior to rituximab and identified immunization opportunities.